Artificial Intelligence in English Language Teaching: A Systematic Literature Review of Tools, Impact, and Challenges - Syuhra, Muhammad Nazaruddin; Chandra, Noor Eka; Rosalina, Elsa (Universitas Hamzanwadi, 2025)
Artificial Intelligence (AI) has emerged as a transformative force in English Language Teaching (ELT), offering innovative tools to enhance proficiency across writing, speaking, listening, and reading skills. However, despite increasing interest, systematic investigations into how AI is currently applied and the challenges it presents in ELT remain scarce. This systematic literature review (SLR) critically synthesizes 35 peer-reviewed articles published between 2021 and 2025, selected from Scopus and SINTA 2-indexed journals using PRISMA guidelines and predefined inclusion criteria. The analysis identifies five categories of AI applications in ELT—pronunciation enhancement, writing assistance, speaking practice, listening comprehension, and personalized learning—alongside tools such as ChatGPT, Grammarly, ELSA Speak, and Duolingo. These tools demonstrate measurable improvements in learners’ linguistic accuracy, fluency, and engagement. Nonetheless, the review highlights persistent challenges, including teacher dependency, ethical concerns, limited contextual awareness by AI systems, fluctuating student motivation, and infrastructure constraints. To address these issues, the study underscores the importance of establishing ethical standards, expanding teacher training, ensuring equitable technological access, and encouraging the development of culturally adaptive AI systems. Cross-sector collaboration among educators, researchers, developers, and policymakers is vital to fully realize the pedagogical potential of AI in English language education.